2011
DOI: 10.1063/1.3544679
|View full text |Cite
|
Sign up to set email alerts
|

Escorted free energy simulations

Abstract: We describe a strategy to improve the efficiency of free energy estimates by reducing dissipation in nonequilibrium Monte Carlo simulations. This strategy generalizes the targeted free energy perturbation approach [Phys. Rev. E. 65, 046122, 2002] to nonequilibrium switching simulations, and involves generating artificial, "escorted" trajectories by coupling the evolution of the system to updates in external work parameter. Our central results are:(1) a generalized fluctuation theorem for the escorted trajector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…The reliability of the calculation relies on the choice of the paths selected to calculate the average in Eq. (1) [33][34][35]. As mentioned above, by associating to the variation of h α,β the relaxation of the sphere configurations, it is possible to prevent overlap of the hard cores to interrupt the transition from one phase to the other.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of the calculation relies on the choice of the paths selected to calculate the average in Eq. (1) [33][34][35]. As mentioned above, by associating to the variation of h α,β the relaxation of the sphere configurations, it is possible to prevent overlap of the hard cores to interrupt the transition from one phase to the other.…”
Section: Resultsmentioning
confidence: 99%
“…In molecular simulations, non-equilibrium methods tend to be less efficient than optimized equilibrium methods as a tool to calculate free energies [18,58]. However, as discussed above, the optimization of non-equilibrium sampling methods is an area of active research, in particular, using importance sampling methods involving path reweighting [49,50,[55][56][57][58][59] and nonlinear maps [69,70]. Moreover, non-equilibrium methods can provide valuable insight into the mechanism underlying a process.…”
Section: Applicationsmentioning
confidence: 99%
“…(3)); the two additional terms roughly account for the change in energy and entropylike phase space compression due to the influence of u λ . It has been shown that these dynamics satisfy a fluctuation theorem, 25 with a modified definition of work given by Eq. (23).…”
Section: Velocity Rescaling and Other Escorted Switching Dynamicsmentioning
confidence: 99%